History and Historiography of Origin and Development of Maiduguri Borno State, Nigeria - Iyanda Kamoru (International Journal of Trends in Humanities, 2024)
This study discussed the history of Maiduguri as pertain to its growth, economic, educational development and its administrative structure. Materials for the work were mainly retrieved from the library where extant work attributed to some to some scholarly sources were used. The internet was also a useful source as some scholarly papers placed there helped a great deal. In essence, this library research that relied heavily on previous research on the subject of study. Maiduguri, a city in Northeastern Nigeria is relatively a new city of about 100 years of History. The city owed its existence to the quest of the British colonialists for a suitable administrative Headquarters to what became colonial Borno after. British conquest. The city became a fast-developing city especially after independence, first, as a provincial capital supervised by the regional government in Kaduna; and as a state capital since 1967. The city’s commercial prowess is not in doubt as it is one of the most endowed commercial cities in Nigeria. The city's infrastructure, business, and educational sectors have all seen tremendous growth and development. Its severe and peaceful ambience earned it the epithet ‘’ Home of Peace’’. Alas, that tag was tampered with by religious crisis in 2006 when there was a riot against the Danish Newspaper Cartoons that depicted the Prophet of Islam in bad light. But more menacing in the Boko Haram insurgency that has its epicentre from the city and now a National and International problem.
Keywords: British conquest; Maiduguri; commercial activities; economic development; educational growth